2011
DOI: 10.1590/s1516-05722011000100014
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação de substratos orgânicos na produção de mudas de hortelã (Mentha gracilis R. Br. e Mentha x villosa Huds.)

Abstract: Avaliação de substratos orgânicos na produção de mudas de hortelã (Mentha gracilisR Palavras-chave: Mentha gracilis, Mentha x villosa, plantas medicinais, substratosABSTRACT: Evaluation of organic substrates on mint (Mentha gracilis R. Br. and Mentha x villosa Huds.) seedling production. The determination of viable alternative substrates is of great importance for the production of medicinal seedlings since the use of residues from agricultural activities represents an alternative to solve environmental and so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 4 publications
0
1
0
2
Order By: Relevance
“…Botucatu-SP, 2019. Segundo Paulus et al (2011), levando em consideração os fatores importantes a serem observados no processo de produção de mudas de boa qualidade, os substratos representam fator primordial. Daniel et al (1997) Em estudo utilizando a mistura de substratos realizado por Gazola et al (2015) mostraram que a utilização de Fibra de coco com substratos comerciais foi uma alternativa importante na produção de mudas de alface (Lactuca sativa L.), pois, essa mistura além de diminuir o uso do produto comercial, potencializa as características que são desejadas para mudas.…”
Section: Resultsunclassified
“…Botucatu-SP, 2019. Segundo Paulus et al (2011), levando em consideração os fatores importantes a serem observados no processo de produção de mudas de boa qualidade, os substratos representam fator primordial. Daniel et al (1997) Em estudo utilizando a mistura de substratos realizado por Gazola et al (2015) mostraram que a utilização de Fibra de coco com substratos comerciais foi uma alternativa importante na produção de mudas de alface (Lactuca sativa L.), pois, essa mistura além de diminuir o uso do produto comercial, potencializa as características que são desejadas para mudas.…”
Section: Resultsunclassified
“…Na espécie Mikania glomerata Spreng., nota-se a formação de raízes independente da adição de matéria orgânica (vermicomposto) (Vidal et al, 2006). Verifica-se a necessidade de fazer a mistura de componentes e selecionar a melhor combinação para encontrar o substrato que atenda as características físicas e nutricionais exigidas pelas mudas (Paulus et al 2011).…”
Section: Resultsunclassified
“…For apical cuttings, the CPS substrate promoted higher NL, which was statistically different from all other substrates. Paulus et al (2011), when evaluating the best organic substrates for the production of Mentha gracilis R. Br. and Mentha x villosa Huds seedlings for field cultivation, found that the commercial substrate Plantmax ® provided the highest average number of leaves in cuttings in all evaluation periods, which were seven, 14 and 21 days after experiment establishment.…”
Section: Substratementioning
confidence: 99%